ダイ47ジ ナンキョク チイキ カンソクタイ エットウ ホウコク 2006-2007 - 神山, 孝吉; カミヤマ, コウキチ; Kamiyama, Kokichi (2008)
P(論文) 第47次日本南極地域観測隊越冬隊は,隊員36名が昭和基地で越冬し,第期5カ年計画の最終年次にあたる定常観測,モニタリング研究観測を継続して行うとともに,宙空系,気水圏系,地学系,生物・医学系のプロジェクト研究観測を昭和基地とドームふじ基地において実施した.また設営関係では基地の運営を2006年2月1日から2007年1月31日まで担当し,電力,上下水道,燃料,通信,食料,医療といった生活基盤の維持管理に加え,車両整備,機械設備工事,LANの運用,野外観測支援など多くの作業を行った.野外観測では5月のブリザードによってオングル海峡の海氷の一部が流出,極夜の明けた7月から温存された海氷ルートの積極的な利用とさらなる延長を計画した.その後,8月以降から気水圏・地圏・生物圏関連の多くのリュツォ・ホルム湾沿岸調査旅行や内陸旅行を実施し,さらに夏期観測時に昭和基地外に集積した廃棄物などを海氷上を輸送して基地内へ持込み整理,処理した.2007年は日本の南極観測50周年にあたり,国内で行われた様々な関連事業を運用3年目にあたるインテルサット衛星通信設備を利用し,第45次及び第46次越冬隊の資料を参考にしながら昭和基地から支援した. The 47th Japanese Antarctic Research Expedition (JARE-47) wintering party, consisting of 36 members, conducted the last year program of the VIth five-year plan of JARE at Syowa Station and inland Dome Fuji Station. The program included observations in meteorology, upper atmosphere physics, atmospheric sciences, glaciology, geophysics, biology and medical science, as well as logistic activities to support the observations and maintain the station from February 1, 2006 to January 31, 2007. A blizzard occurring in May blew some of sea ice around Syowa Station and Ongul Strait to open sea, and the aggressive field activities started in July, taking care of sea ice condition. Many field activities in the atmosphere, hydrosphere, geosphere and biosphere were carried out in the coastal area of east Lutzow-Holm Bay, as well as the inland plateau between Dome Fuji and Syowa Stations. Waste and stockpile, accumulated during the last summer season, were gathered and organized in Syowa Station during winter season over sea ice. The year 2007 marked the 50th anniversary of the Japanese Antarctic Research Expedition, and we supported related events held in the mother country through an Intelsat satellite connection which got more familiar after 2 years experience of late wintering parties (JARE-45 and JARE-46). departmental bulletin paper